Chorioamniontis in preterm delivery is associated with degradation of decorin and biglycan and depletion of hyaluronan in fetal membranes. - Meinert, M; Malmström, Anders ; 0000-0002-6691-146X; Petersen, A C; Eriksen, G V; Uldbjerg, N (Placenta, 2014)
The proteoglycan decorin stabilizes collagen whereas biglycan and hyaluronan disrupt well-organized collagen. The aim was to determine the concentrations of these constituents in fetal membranes in relation to gestational age, preterm labour, PPROM and chorioamnionitis.